Thymectomy effect on gonadotropins in prepubertal and Pubertal guinea pigs - P. MURALI; J. RADHIKA; D. ALWIN (International Journal of Pharma and Bio Sciences, 2018)
In the present investigations we would like to find out the Thymectomy effects on gonadotropins at pre pubertal (5th week) and pubertal (9th week) stages in male and female guinea pigs of both sex. The serum hormonal level of gonadotropins was determined in the thymectomized and sham operated animals before the procedure, at the end of 30th day and 60th day after the procedure. Serum Luteinizing Hormone (LH) level did not show any significant changes in thymectomy of both male and female guinea pigs except at 60th day of pubertal female. Serum level of Follicle Stimulating Hormone (FSH) was significantly reduced in the male and female guinea pigs at the end of 30th and 60th day of age in all groups. The body weight was measured at regular intervals. The above results clearly indicate the thymic endocrine influence on gonadotropins levels.